Wide-field subdiffraction RESOLFT microscopy using fluorescent protein photoswitching. - Schwentker, M; Bock, H; Hofmann, M; Jakobs, S; Bewersdorf, J; Eggeling, C; Hell, S (2007)
Subdiffraction fluorescence imaging is presented in a parallelized wide-field arrangement exploiting the principle of reversible saturable/switchable optical transitions (RESOLFT). The diffraction barrier is overcome by photoswitching ensembles of the label protein asFP595 between a nonfluorescent off- and a fluorescent on-state. Relying on ultralow continuous-wave intensities, reversible protein switching facilitates parallelized fast image acquisition. The RESOLFT principle is implemented by illuminating with intensity distributions featuring zero intensity lines that are further apart than the conventional Abbe resolution limit. The subdiffraction resolution is verified by recording live Escherichia coli bacteria labeled with asFP595. The obtained resolution of 50 nm ( approximately lambda/12) is limited only by the spectroscopic properties of the proteins and the imperfections of the optical implementation, but not on principle grounds.